PERAN LEMBAGA PERKREDITAN DESA DALAM UPAYA MENSEJAHTERAKAN MASYARAKAT MELALUI PROGRAM KREDIT PERUMAHAN KRAMA DESA KEDONGANAN - Yovie Virgan, I Kadek; Sastra Wijaya, Komang Adi; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2021)
(KRURA) is able to make the community more prosperous. However, as time goes by and the business activities of the Kedonganan Traditional Village LPD grow, the trust of the local customs and customers continues to grow. Kedonganan who wants to have his own house. Then the Krama Housing Credit (Krura) program was launched by the Kedonganan Traditional Village LPD. In addition, this Krura also aims to save or Bali's palemahan from foreign investor and outsiders. The three concepts will lead to three goals, namely trust, integrity and professionalism. With strong trust, LPD can be strong. Trust is a social capital for the Kedonganan Traditional Village LPD. The integrity of the LPD management and employees must be directed at the progress of the institution and the village, so that community integrity is expected to emerge towards the LPD. While professionalism is the key to the birth of trust and integrity.